2006
DOI: 10.1002/jmv.20647
|View full text |Cite
|
Sign up to set email alerts
|

Protection against influenza virus infection by intranasal vaccine with surf clam microparticles (SMP) as an adjuvant

Abstract: A safe and effective adjuvant is necessary to enhance mucosal immune responses for the development of an inactivated intranasal influenza vaccine. The present study demonstrated the effectiveness of surf clam microparticles (SMP) derived from natural surf clams as an adjuvant for an intranasal influenza vaccine. The adjuvant effect of SMP was examined when co-administered intranasally with inactivated A/PR8 (H1N1) influenza virus hemagglutinin vaccine in BALB/c mice. Administration of the vaccine with SMP indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 30 publications
1
11
0
1
Order By: Relevance
“…These findings were consistent with results showing the protective effects against avirulent influenza virus (A/ PR8, H1N1) infection in mice by intranasal administration of chitin microparticles into the lung (unpublished data by P. Strong). It is previously reported that chitin microparticles had a mucosal adjuvant effect when coadministered with an influenza hemagglutinin vaccine and increased both the mucosal and systemic humoral responses that provided complete protection against challenge with the homologous influenza virus H1N1 or H5N1 in mice Asahi-Ozaki et al, 2006;Ichinohe et al, 2006]. The current study demonstrates hitherto unrecognized effects of chitin microparticles in enhancing innate protection against infection with a highly pathogenic avian influenza virus strain.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…These findings were consistent with results showing the protective effects against avirulent influenza virus (A/ PR8, H1N1) infection in mice by intranasal administration of chitin microparticles into the lung (unpublished data by P. Strong). It is previously reported that chitin microparticles had a mucosal adjuvant effect when coadministered with an influenza hemagglutinin vaccine and increased both the mucosal and systemic humoral responses that provided complete protection against challenge with the homologous influenza virus H1N1 or H5N1 in mice Asahi-Ozaki et al, 2006;Ichinohe et al, 2006]. The current study demonstrates hitherto unrecognized effects of chitin microparticles in enhancing innate protection against infection with a highly pathogenic avian influenza virus strain.…”
Section: Discussionsupporting
confidence: 52%
“…This prophylactic effect is elicited by activation of natural killer cells and regulation of inflammatory cytokines such as IL-6 and interferon-gamma-inducible protein-10 (IP-10). The adjuvant effects of chitin microparticles are also expected Asahi-Ozaki et al, 2006;Ichinohe et al, 2006] in inducing adaptive immunity following infection. Identification of therapeutic innate immunity enhancing agents such as chitin microparticles may lead to antiviral strategies against the highly pathogenic H5N1 influenza virus and may have relevance as part of a first line defense against H5N1 outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in different mouse studies that i.n. vaccination with adjuvanted WIV (Joo et al, 2010) or split viruses (Ichinohe et al, 2005;Ichinohe et al, 2006;Saluja et al, 2010) effective induction of serum IgG titers (Tseng et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Although these toxins effectively provoke mucosal immune responses, they elicit adverse clinical side effects, such as nasal discharge and the facial paralysis of Bell's palsy [Mutsch et al, 2004]. Therefore, other adjuvants that are both effective and safe for human use have been developed for clinical application with intranasal influenza vaccine [Coulter et al, 2003;Hasegawa et al, 2005;Ichinohe et al, 2005Ichinohe et al, , 2006Ichinohe et al, , 2007aAsahi-Ozaki et al, 2006].…”
Section: Introductionmentioning
confidence: 99%